Does Peer Rejection Moderate the Associations among Cyberbullying Victimization, Depression, and Anxiety among Adolescents with Autism Spectrum Disorder? - Michelle F. Wright; Sebastian Wachs (MDPI AG, 2019)
While the consequences of cyberbullying victimization have received some attention in the literature, to date, little is known about the multiple types of strains in adolescents’ lives, such as whether cyberbullying victimization and peer rejection increase their vulnerability to depression and anxiety. Even though some research found that adolescents with disabilities show higher risk for cyberbullying victimization, most research has focused on typically developing adolescents. Thus, the present study focused on examining the moderating effect of peer rejection in the relationships between cyberbullying victimization, depression, and anxiety among adolescents with autism spectrum disorder. There were 128 participants (89% male; ages ranging from 11–16 years old) with autism spectrum disorder in the sixth, seventh, or eighth grade at 16 middle schools in the United States. Participants completed questionnaires on cyberbullying victimization, peer rejection, depression, and anxiety. Results revealed that cyberbullying victimization was associated positively with peer rejection, anxiety, and depression among adolescents with autism spectrum disorder. Further, peer rejection was linked positively with depression and anxiety. Peer rejection moderated the positive relationship between cyberbullying victimization and depression, but not anxiety. Implications for prevention programs and future research are discussed.